The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/978-3-642-14363-2_17
|View full text |Cite
|
Sign up to set email alerts
|

Managing Learner’s Affective States in Intelligent Tutoring Systems

Abstract: Abstract. Recent works in Computer Science, Neurosciences, Education, and Psychology have shown that emotions play an important role in learning. Learner's cognitive ability depends on his emotions. We will point out the role of emotions in learning, distinguishing the different types and models of emotions which have been considered until now. We will address an important issue concerning the different means to detect emotions and introduce recent approaches to measure brain activity using Electroencephalogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 40 publications
0
15
0
3
Order By: Relevance
“…It shows three emotion types (Happiness/Satisfaction, Shame, and Anger) that appear as the conversation evolves through exchange types (such as ascertain-information, elicit-information and giveinformation) produced by the participants. As we can also observe in these examples, emotion and cognition are closely linked (Frasson & Chalfoun, 2010).…”
Section: Emotion Awarenessmentioning
confidence: 89%
See 1 more Smart Citation
“…It shows three emotion types (Happiness/Satisfaction, Shame, and Anger) that appear as the conversation evolves through exchange types (such as ascertain-information, elicit-information and giveinformation) produced by the participants. As we can also observe in these examples, emotion and cognition are closely linked (Frasson & Chalfoun, 2010).…”
Section: Emotion Awarenessmentioning
confidence: 89%
“…They are experienced in various situations and serve a variety of functions in the academic environment including promoting or undermining behavioral and cognitive engagement, self-regulation of learning activities and achievement (Linnenbrink-Garcia & Pekrun, 2011). Learning involves three particular cognitive processes, attention, memory and reasoning; with respect to each of them, students' cognitive ability depends on their emotions (Frasson & Chalfoun, 2010). According to them, emotions can be used in the learning context to increase students' attention as well as to improve memory and reasoning.…”
Section: Emotion Awarenessmentioning
confidence: 99%
“…In [23] the researchers attempt to dive deeper into the affective state of the learner by gathering, in their own words, the definition of what they mean by "engagement in courses" and "What makes a course engaging to you?" The learners in this study were male and female freshman and sophomores in engineering, and the researchers were able to group the responses into categories, as well as give specific wording terms that the students used.…”
Section:  mentioning
confidence: 99%
“…Studies have shown that emotional experiences influence student's motivation, learning strategies and achievement whereas such emotional experiences are influenced by personality and classroom characteristics (Frasson & Chalfoun 2010;Goetz et al 2006). …”
Section: Introductionmentioning
confidence: 99%